Paradoxical Language Dominance in a Bilingual Child with Autism Spectrum Disorder - Garcia-Serrano, A (SAGE Publications Ltd, 2025)
Research question: Beyond socio-interactive and behavioral deficits, children with autism spectrum disorder (ASD) often show exceptional cognitive capacities. Incipient evidence shows that these may involve elevated second-language (L2) learning abilities. Yet, research is scant and existing reports have targeted broad receptive and productive skills, prompting an unexplored question: How do elevated L2 skills in ASD manifest across overlooked domains, such as vocabulary and pragmatics? Methodology: We report on the case of LC, an 11-year-old Chilean child with ASD who learned English via minimal audiovisual exposure in a fully Spanish-speaking environment. Data and analysis: Our protocol included systematic assessments of language exposure and development, neuropsychological outcomes, and bilingual tests of language production and comprehension as well as syntactic, semantic, translation, vocabulary, and prosodic skills. Findings: LC exhibited high L2 (English) abilities despite null social interactions in this language, alongside lower first-language (Spanish) skills despite constant exposure. His L2 abilities were most notable in speech fluency, pronunciation, and vocabulary. Originality: This is the first report of exceptional L2 skills in ASD including fine-grained measures of multiple linguistic and pragmatic domains. The uniqueness of this case adds to a rare corpus of paradoxical language dominance in children with this condition. Significance: LC’s paradoxical dominance may reflect a preference for engaging, non-socially mediated stimuli, inviting reconsiderations of language learning patterns in ASD. © The Author(s) 2025.